Study Literature Review : Client Centered Therapy - Calisa Najwa Vionita; Helmi Salma Napisa; Ita Rosadi; Pitri Liani; Yanuar Syaiful Anwar; Nuram Mubina (Empowerment Jurnal Mahasiswa Psikologi Universitas Buana Perjuangan Karawang, 2025)
This article examines the Client-Centered Therapy (CCT) approach developed by Carl Rogers, a humanistic psychotherapeutic method that views individuals as creative beings with an inherent potential for self-development. Central to this approach is the conviction that clients can achieve psychological growth and self-actualization if the therapist provides three essential conditions: congruence (genuineness), unconditional positive regard, and accurate empathy. The therapeutic process is conducted through systematic stages, beginning with rapport building and free problem exploration, leading to the attainment of self-insight and client autonomy in addressing issues realistically. Through a case study of a client with severe depression, the application of CCT was proven effective in providing emotional relief, enhancing self-awareness of personal worth, and fostering more adaptive behavioral changes following a series of structured sessions.. Artikel ini mengulas pendekatan Client-Centered Therapy (CCT) yang dikembangkan oleh Carl Rogers, sebuah metode psikoterapi humanistik yang memandang individu sebagai pribadi kreatif dengan potensi pengembangan diri internal. Inti dari pendekatan ini adalah keyakinan bahwa klien dapat berkembang secara psikologis dan mencapai aktualisasi diri jika terapis menghadirkan tiga kondisi utama: kongruensi (kejujuran), penerimaan positif tidak bersyarat, dan empati yang akurat. Proses terapi dilakukan melalui tahapan sistematis yang dimulai dari pembangunan rapport, penjajakan masalah secara bebas, hingga pencapaian self-insight dan kemandirian klien dalam menyelesaikan masalahnya secara realistis. Melalui studi kasus pada klien dengan depresi berat, penerapan CCT terbukti efektif memberikan kelegaan emosional, meningkatkan kesadaran diri sebagai individu yang berharga, serta menghasilkan perubahan perilaku yang lebih adaptif setelah menjalani serangkaian sesi yang terstruktur.